2014
DOI: 10.5194/nhess-14-1517-2014
|View full text |Cite
|
Sign up to set email alerts
|

Empirical atmospheric thresholds for debris flows and flash floods in the southern French Alps

Abstract: Abstract. Debris flows and flash floods are often preceded by intense, convective rainfall. The establishment of reliable rainfall thresholds is an important component for quantitative hazard and risk assessment, and for the development of an early warning system. Traditional empirical thresholds based on peak intensity, duration and antecedent rainfall can be difficult to verify due to the localized character of the rainfall and the absence of weather radar or sufficiently dense rain gauge networks in mountai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…The differences may be due to the proxies being associated with different atmospheric conditions. The QCAPE-proxy is representative of short-lasting convective rainfall systems existing in a mesoscale humid environment triggering debris flows (Turkington et al 2014). The rain-proxy includes all synoptic conditions producing sufficient rainfall to trigger a debris flow as it is based on observational records.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The differences may be due to the proxies being associated with different atmospheric conditions. The QCAPE-proxy is representative of short-lasting convective rainfall systems existing in a mesoscale humid environment triggering debris flows (Turkington et al 2014). The rain-proxy includes all synoptic conditions producing sufficient rainfall to trigger a debris flow as it is based on observational records.…”
Section: Resultsmentioning
confidence: 99%
“…As rain gauges are very local and often non-catchment representative, the QCAPE-proxy was used to mimic the mesoscale atmospheric conditions leading to heavy local convective precipitation. Turkington et al (2014) showed that a QCAPE-based proxy could outperform daily precipitation and multiple day precipitation amounts as a proxy for debris flows in the Barcelonnette Basin. QCAPEproxy was derived from ERA-Interim reanalysis dataset, for the period 1979-2011 (Dee et al 2011).…”
Section: Meteorological Proxies For Debris Flowsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Toreti et al (2013) showed that debris-flow occurrence in the southern Swiss Alps, exhibits a distinct pattern in large-scale atmospheric circulation and suggested that this information can be used to improve existing warning systems. On this line, Turkington et al (2014), in a study centered on the southern French Alps, showed that empirical thresholds can be directly identified based on regional atmospheric patterns. Second, linking debris-flow occurrence with seasonal and meteorological characteristics may provide indications on the potential impact of climate change on debris-flow activity .…”
Section: Introductionmentioning
confidence: 99%